The impact of obstacles to applying international financial reporting standards (IFRS) on the quality of financial reports in economic units in the Kurdistan Region of Iraq - Emad Jawdat Noori; Taman Shwan Sabir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This study aims to determine the impact of obstacles to the application of international financial reporting standards IFRS on the quality of financial reports in the economic units in the Kurdistan Region of Iraq. To achieve the aim of the study, the researcher presented the problem of the study and some previous studies related to the application of international financial reporting standards (IFRS) on the quality of financial reports.In addition to the main concepts associated with financial reporting standards. and characteristics of the quality of financial reports. The researcher relied on conducting an exploratory study by designing a survey list to test the hypotheses of the study, and it was distributed to a sample of auditors in Erbil, Iraq, and the hypothesis of the study was tested using the SPSS statistical program. The study concluded that removing the obstacles to the application of international financial reporting standards helps to achieve the quality of the financial statements.